In vitro antibacterial and antioxidant activities of betel leaf mediated synthesized silver nanoparticles - MANIKANTA Y,; CHANDRAPPA C.P,; CHANDRASEKHAR N, (International Journal of Pharma and Bio Sciences, 2017)
An advanced approach for the synthesis of silver nanoparticles (AgNPs) is of appreciable importance because of its tremendous scope of applications in distinct fields including drug delivery and diagnostics. The presented study reported the synthesis and characterization of silver nanoparticles by Piper betel leaves extract and their potential biological evaluation. The main aim was to expand an inexpensive and eco-friendly synthesis technique of silver nanoprticles using aqueous extracts of Piper betel as a reducing and capping agent which has exhibited effect against pathogens such as Staphloccocus sp., Pseudomonas sp. and proven significant antioxidant activity. The betel leaves were collected and shade dried. The dried leaves powder was subjected to prepare extracts and which were used for the synthesis of silver nanoparticles. The synthesized nanoparticles were then further characterized by using techniques such as UV-visible spectroscopy, scanning electron microscope (SEM), energy-dispersive x-ray spectroscopy (EDS) and X-ray diffraction pattern (XRD) analysis. The average size of nanoparticles was found to be 22 nm. The in vitro antibacterial assay had shown the maximum activity against Staphylococcus sp., Pseudomonas sp. Antioxidant activity of synthesized silver nanoparticles in DPPH and FRAP assay shown maximum activity i.e., 84.048% and 99.109% respectively at 250 μl/ml concentrations. It can be concluded that the extracts of Piper betel leaves could be a better source of materials for the synthesis of silver nanoparticles which exhibited antibacterial activity against tested organisms. Significant results of this study will be opened a door for the development novel drugs from the Piper betel to treat various diseases.